Effect of Row Spacing and Green Leaf Cuttings on Seed Yield and its Contributing Attributes in Coriander - HARMANJIT KAUR; DEEPAK ARORA; RAJINDER SINGH (Seed Research, 2026)
A field investigation was carried out to evaluate the effect of varying row spacing and green leaf cuttings on seed yield and its contributing traits in coriander cultivar ‘Punjab Sugandh’for two years (2016-17 and 2017-18) at University Seed Farm, Ladhowal of Punjab Agricultural University, Ludhiana, Punjab. The experiment was laid out in split plot design with 12 treatments comprising three inter row spacing (30, 45 and 60 cm) and varying number of leaf cuttings (no cut, one, two and three cuttings). The highest green leaf yield was obtained from plants in 30 cm row spacingand three leaf cuttings. Maximum plant height was recorded with narrow spacing of 30 cm and with no cutting. The maximum expression of number of primary, secondary shoots per plant and stem diameter was observed with 60 cm spacing and one leaf cutting. However, the leaf area was observed to be maximum with widely spaced plants from where no green leaf cutting was taken. The highest seed yield was obtained with 30 cm spacing and one leaf cutting. The studies implicated that the closer spacing of 30 cm significantly reduced the vegetative growth and green leaf yield of the crop whereas it was beneficial for improvement in seed yield. On the other hand the wider spacing improved the vegetative growth of crop but the seed yield was compromised with the wider spacing. The treatment combination of one green leaf cutting with planting in 30 cm row spacing proved to be the best for seed yield with added advantage of green leaf cutting.